Cigarette use, anxiety, and insomnia from adolescence to early adulthood: A longitudinal indirect effects test. (September 2021) - Bilsky, Sarah A.; Luber, Maxwell J.; Cloutier, Renee M.; Dietch, Jessica R.; Taylor, Daniel J.; Friedman, Hannah P.
Highlights: Cigarette use during adolescence is associated with increased risk for insomnia during adulthood. Cigarette use is associated with increased anxiety symptoms characterized by physiological arousal, and anxiety symptoms and insomnia are bidirectionally associated. Anxiety symptoms characterized by physiological arousal exert an indirect effect on the association between cigarette use during adolescence and insomnia symptoms in early adulthood. The associations remained after adjusting for baseline depressive symptoms, health, and alcohol use. Abstract: Background: Cigarette use during adolescence has been linked to increased risk for insomnia symptoms, but limited work has examined factors that may account for this association. Adolescent cigarette use and anxiety symptoms characterized by physiological hyperarousal evidence bidirectional associations, as do anxiety symptoms and insomnia symptoms. This suggests that adolescent cigarette use, anxiety symptoms characterized by physiological hyperarousal, and insomnia symptoms may increase and maintain one another. The current study tests physiological hyperarousal anxiety symptoms as a potential indirect effect in the cigarette-insomnia symptoms link across adolescence and young adulthood. Methods: We examined data from adolescents and young adults from Waves 1, 2, 3 and 4 of the National Longitudinal Study of Adolescent to Adult Health ( N = 2, 432 with full data). Insomnia symptoms were assessed at baseline (ages 12–16 years), 1 year later (13–17 years), and 14 years after baseline (26 – 30 years) among a nationally representative sample of adolescents. Cigarette use was assessed at baseline, 1 year later, 6 years after baseline, and 14 years after baseline. Anxiety symptoms were assessed at baseline and 1 year later. Results: Structural equation models indicated that anxiety symptoms exerted an indirect effect on the longitudinal associations between adolescent cigarette use and adult insomnia symptoms. Anxiety symptoms and cigarette use evidenced bidirectional associations during adolescence. Conclusions: These results suggest that increases in anxiety symptoms characterized by physiological hyperarousal may be one mechanism whereby cigarette use during adolescence is associated with increased insomnia symptoms during early adulthood. Prevention efforts aimed at reducing cigarette use during adolescence may have long term additional benefits for anxiety symptoms and insomnia symptoms.